Parents’ Feelings About Preterm Birth And Cooperation With Nurses In Hospital - Pociutė, Edita; Liutikienė, Rasa; Stoukuvienė, Žaneta (Slauga. Mokslas ir praktika, 2021)
Aim of the study: to analyse parents’ feelings about preterm birth and cooperation with nurses in hospital. Research methods. After the analysis of scientific sources, a quantitative research was conducted - online written survey from 26-11-2020 to 21-12-2020, in the focused groups "Klaipėda premature babies", "Mothers", "Premature babies", "Premature babies and Mothers’ Fears", "Natural Motherhood", "Helping to Grow". The study involved 106 parents who had premature births in the last two years and had been admitted to hospital for more than 48 hours. SPSS version 24.0 was used for the statistical analysis of the study data. Results. The majority of the participants were women (68,9%), more than half of the parents (51,9%) were aged between 31 and 40 years, and the majority of the participants had a university degree. For more than a third of the participants this was their first birth. The study showed that the majority of parents of preterm newborns were afraid for their child’s health/life (4.41±0.85) and sad that they could not be with their child all day (4±0.97). The most important factors for parents to cooperate with nurses were pleasant communication (4.68±0.54), sharing of experience (4.65±0.68), taking responsibility (4.65±0.82) and timely information (4.63±0.64). Slightly less important for parental cooperation are individual personal characteristics (4.5±0.96) and personal attitudes (4.3±1.12). Conclusions. Parents with a premature newborn feel fear for their child’s health/life and sad that they cannot spend all their time together. When caring for a premature newborn in hospital, the following factors are important for cooperation with nurses: pleasant communication, sharing of experience, taking responsibility and timely information.